Pizarnik: la lengua extranjera como posibilidad de lo intimo - Raphaëlle Hérout (Cuadernos LIRICO)
We wish to study the poetic voice sought by Pizarnik, by analyzing her relation to language, via the different representations of the languages, then the way in which the search for a new linguistic space allows, through the conjunction of language and silence, to create a shelter for the intimate. This intimacy is paradoxical from the outset, because it is made possible by the words of her chosen poets who open up her voice. The final question is to see how the thought tries to anchor itself in the interstices of a language experienced as a perceptive matrix able to combine desire and reality.